If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -1(4x + 9) = 3x + -35 Reorder the terms: 9x + -1(9 + 4x) = 3x + -35 9x + (9 * -1 + 4x * -1) = 3x + -35 9x + (-9 + -4x) = 3x + -35 Reorder the terms: -9 + 9x + -4x = 3x + -35 Combine like terms: 9x + -4x = 5x -9 + 5x = 3x + -35 Reorder the terms: -9 + 5x = -35 + 3x Solving -9 + 5x = -35 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -9 + 5x + -3x = -35 + 3x + -3x Combine like terms: 5x + -3x = 2x -9 + 2x = -35 + 3x + -3x Combine like terms: 3x + -3x = 0 -9 + 2x = -35 + 0 -9 + 2x = -35 Add '9' to each side of the equation. -9 + 9 + 2x = -35 + 9 Combine like terms: -9 + 9 = 0 0 + 2x = -35 + 9 2x = -35 + 9 Combine like terms: -35 + 9 = -26 2x = -26 Divide each side by '2'. x = -13 Simplifying x = -13
| 60=6(2x-4) | | 3x^2+bx+1=0 | | 2k-1.2=3.6 | | Y=2(6)-13 | | -6+2p=1+3p | | P=B+3A | | 2x^2=300 | | 15y+3x=45 | | v=2+2 | | 9b-3=33 | | -6-7m=71 | | 23-9x+7x=21 | | 3+4y=y-8 | | 5=.33x | | 3h-6=15 | | Y=.33(0) | | Y=.33(-12) | | .25x-8=6 | | 9-10q=-6-7q | | 7/6-5/8=2 | | 10x^3-17x^2-6x= | | 5r+3=18 | | 5x+7=-127 | | -5=-y+2 | | 4x-5y=-8 | | -b=-8+b | | 5x-7=-127 | | X=-0+2 | | (3)=-7x | | 3=-7x | | -7+k/5=-5 | | 1+5b=-19 |